Perception of Students Syiah Kuala University on the Islamic Shari'a Implementation in Banda Aceh - Zulfa Fadhillah.N, Rayhan; Firdaus, Roni; Abdul Azizsyah, Maulana (BELIEF: Sociology of Religion Journal, 2024)
Aceh is a region in Indonesia that implements Sharia Law as its legal foundation. However, violations of this policy, particularly among youth, remain prevalent. Understanding students' perceptions of this implementation is crucial, as they play a pivotal role as agents of social change. This study employs a descriptive quantitative survey approach, using a purposive sampling method to collect data from 95 students at the Faculty of Social and Political Sciences, Syiah Kuala University (FISIP USK). Data were gathered through a structured questionnaire with Likert-scale responses, focusing on three indicators: understanding, attitudes, and evaluation of Sharia Law implementation. The findings reveal that students generally have a positive perception of Sharia Law, with 66.3% expressing agreement regarding its understanding, 66.3% showing support in their attitudes, and 65.1% positively evaluating its implementation. The study underscores the influence of personal experiences, social environments, and media exposure on shaping perceptions. It also emphasizes the need for improved education on Sharia Law and collaborative efforts between the government and educational institutions to enhance awareness and adherence among youth. This research contributes to understanding the dynamics of Sharia Law implementation in Aceh, offering insights for policymakers to strengthen legal education for youth